Factors associated with e-cigarette use among vocational students: A cross-sectional multistage cluster survey, Thailand - Sarunya Benjakul; Saroj Nakju; Lakkhana Termsirikulchai (Tobacco Induced Diseases, 2023)
Introduction The use of e-cigarettes has steadily increased, and vocational students are one primary target of e-cigarette marketing. This cross-sectional survey research aimed to explore e-cigarette use and examine the factors associated with it.